Mental Well-being of Albanian and Kosovo Albanian Immigrants - Thartori, Voltisa; Hisham Ismail, Nik A. (2021)
Moving to a new country causes significant challenges for immigrants. Various reasons contributed to immigrants' mental well-being, such as language barriers, lack of family and social support, discrimination, and others that affect well-being and quality of life among immigrants in the host country. This qualitative study explored the lived experiences of 18 Albanian and Kosovo-Albanian immigrants residing in Malaysia. The objectives of this study are as follows: (i) to investigate perceptions of immigrants toward mental well-being; (ii) to explore coping strategies for mental well-being among immigrants; and (iii) to identify suggestions and recommendations of immigrants residing in Malaysia and Australia. Social Learning Theory (SLT) guided this study. SLT focuses on learning through observation and reflection. Therefore, this theory is suitable for the current study since our thoughts, actions and behaviours are influenced by social and cultural factors. This study employed a qualitative phenomenological case study using in-depth semi-structured interviews. The result showed that mental well-being was perceived as physical, mental and spiritual health; accomplishment and life purposes; and contentedness positively affected the immigrants’ mental well-being. The immigrants resorted to several strategies in coping with mental well-being, such as calmness and having a positive attitude in solving their problems. The findings also recommended immigrants embrace a new culture and adapting their life in their host country.